1991
DOI: 10.1105/tpc.3.4.371
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cis-acting sequences regulating root-specific gene expression in tobacco.

Abstract: The expression of the tobacco root-specific gene TobRB7 was characterized. Gel blot hybridizations to RNA isolated from various tobacco tissues demonstrated that steady-state TobRB7 mRNA is not detected in expanded leaf, stem, or shoot apex tissue. To determine the spatial pattern of expression, in situ hybridization to root sections revealed that TobRB7 expression is localized to root meristem and immature central cylinder regions. The 5' flanking region of the gene was studied with respect to its ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(48 citation statements)
references
References 31 publications
4
44
0
Order By: Relevance
“…Consistent observations locate both PIP and TIP expression in the vascular tissue and surrounding cells, including early developmental stages (Yamamoto et al 1991;Kaldenho et al 1995;Yamada et al 1995;Daniels et al 1996). In situ hybridization experiments reveal the highest PIP mRNA levels in the region of Arabidopsis vasculature (Fig.…”
Section: Localization Of Aquaporin Expression As a Guide To Their Rolsupporting
confidence: 74%
“…Consistent observations locate both PIP and TIP expression in the vascular tissue and surrounding cells, including early developmental stages (Yamamoto et al 1991;Kaldenho et al 1995;Yamada et al 1995;Daniels et al 1996). In situ hybridization experiments reveal the highest PIP mRNA levels in the region of Arabidopsis vasculature (Fig.…”
Section: Localization Of Aquaporin Expression As a Guide To Their Rolsupporting
confidence: 74%
“…In this study, PtGA20ox and PtGA2ox1 were expressed under the control of two well-studied promoters, namely LMX5 and TobRB7 , respectively, leading to expression on the xylem side of the cambial zone in the stem (Bjorklund et al ., 2007) and the meristem and central cylinder regions in the root (Yamamoto et al ., 1991). The results show that the precise tissue localization of GAs regulates adventitious root initiation and elongation in tobacco.…”
Section: Introductionmentioning
confidence: 99%
“…Dierent observations indicate that dierential expression of aquaporins regulates water¯uxes in plants. Yamamoto et al (1991) showed that TobRB7, a putative plasma-membrane water channel of tobacco, is highly expressed in the meristem and the immature central cylinder of roots. The tonoplast aquaporin c-tonoplast intrinsic protein (c-TIP; Ludevid et al 1992) and AthH2/AtPIP1b (Kaldenho et al 1995), a plasma-membrane aquaporin, are both expressed in young, developing tissue.…”
Section: Introductionmentioning
confidence: 99%